2014
DOI: 10.1016/j.jval.2014.08.1666
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence-Based Measurement of the Economic Burden of Rare Diseases: Case Review To Determine the Annual Cost of Acromegaly In France

Abstract: Objectives: To assess pill burden, health care resource utilization (HRU), and costs among patients with long-term immediate release (IR) hydrocodone use. MethOds: We performed a retrospective analysis of health care claims from 2011-2012 Truven MarketScan® Commercial, Medicare supplemental, and Medicaid Multistate databases. Patients with IR hydrocodone prescription for ≥ 90 days during 6 month baseline period (July 2011-December 2011) with continuous enrollment during baseline and 12 month follow-up periods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As it can be seen, direct costs (lab tests, medicines, visits, hospitalizations, diagnostic procedures, etc.) are included in all studies, whereas the indirect costs presented as loss of productivity due to acromegaly, unemployment, assistance to perform household chores and family member loss of income are calculated only in a few studies [26,37,42]. This could be highlighted as a strong limitation especially in cost-of-illness studies where the societal perspective is broader and it is usually taken into account.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As it can be seen, direct costs (lab tests, medicines, visits, hospitalizations, diagnostic procedures, etc.) are included in all studies, whereas the indirect costs presented as loss of productivity due to acromegaly, unemployment, assistance to perform household chores and family member loss of income are calculated only in a few studies [26,37,42]. This could be highlighted as a strong limitation especially in cost-of-illness studies where the societal perspective is broader and it is usually taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…Different costs were also reported in different studies, e.g. only 3 out of 33 presented the indirect costs taking into consideration the societal perspective [26,37,42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rare diseases are serious and difficult to diagnose and treat, which can easily lead to damaged tissues and organs, resulting in disability, mental disorders, deteriorated quality of life, and even death. Rare diseases put an extremely heavy burden on patients’ families and society and pose immense challenges in building and improving global public healthcare systems [ 7 9 ]. Research has shown that the annual curative expenditure for Hemophilia in the United States is $80,811–$632,088.…”
Section: Introductionmentioning
confidence: 99%
“…However, only 5% of them have treatment methods [6,7]. Since rare diseases are serious and difficult to diagnose and treat, most of them affect all the systems and organs in the human body, which can easily result in disability, mental disorders, deteriorated quality of life, and even death, causing extremely heavy burdens on patient's families and the society while posing immense challenges to the construction and improvement of the global public health service system [8][9][10]. Researches have shown that the annual curative care expenditure(CCE) of Hemophilia in the United States is US$80,811-632,088; European patients with Multiple Sclerosis (MS) spend an average of US$47,888 per year on curative care [11,12]; in Australia, CCE for rare diseases accounts for 4.60%-10.50% of the total inpatients' curative care expenditure, equivalent to that of diabetes or asthma in 2010 [13].…”
Section: Introductionmentioning
confidence: 99%